2020
DOI: 10.1101/2020.10.16.341776
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparison of morphine, oxycodone and the biased MOR agonist SR-17018 for tolerance and efficacy in mouse models of pain

Abstract: The mu opioid receptor-selective agonist, SR-17018, preferentially activates GTPS binding over beta-arrestin2 recruitment in cellular assays. In mice, SR-17018 stimulates GTPgammaS binding in brainstem and produces antinociception with potencies similar to morphine. However, it produces much less respiratory suppression and mice do not develop antinociceptive tolerance in the hot plate assay upon repeated dosing. Herein we evaluate the effects of acute and repeated dosing of SR-17018, oxycodone and morphine… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 61 publications
(100 reference statements)
0
3
0
Order By: Relevance
“…Moreover, it prevented the onset of morphine withdrawal. However, recent data show that SR-17018 did not reverse morphine tolerance in tail flick assay [86]. These results suggest that SR-17018 may efficiently attenuate some aspects of opioid addictive behavior, but not under all circumstances.…”
Section: Piperidine Benzimidazoles (Sr-compounds)mentioning
confidence: 85%
See 2 more Smart Citations
“…Moreover, it prevented the onset of morphine withdrawal. However, recent data show that SR-17018 did not reverse morphine tolerance in tail flick assay [86]. These results suggest that SR-17018 may efficiently attenuate some aspects of opioid addictive behavior, but not under all circumstances.…”
Section: Piperidine Benzimidazoles (Sr-compounds)mentioning
confidence: 85%
“…As far as their addictive properties are considered, Grim et al [85] have shown that SR-17018 does not induce hot plate antinociceptive tolerance when administered chronically. A recently published study by Pantouli et al [86] was aimed to determine the effectiveness of SR-17018 in mouse models of pain. Under repeated dosing, SR-17018 developed tolerance in the tail immersion test, suggesting that tolerance to antinociceptive effects of SR-17018 may occur when tests measuring spinal reflexes are used.…”
Section: Piperidine Benzimidazoles (Sr-compounds)mentioning
confidence: 99%
See 1 more Smart Citation